Antidiabetic Activity of Ethanolic Extract of Caesalpinia Sappan (Linn). On Alloxan Induced Diabetes Mellitus in Rats. - Sonam Pushkar; Amita Tilak; Pushpendra Pushkar; Yatendra Katiyar; Minakshi Verma; Preeti Bhaduaria (International Journal of Pharma and Bio Sciences, 2023)
India would become the planet's capital of diabetes mellitus by the year 2030. It is treated by conventional oral hypoglycaemic agents like sulphonylureas. One plant used to treat DM in folk medicine and mentioned in ayurvedic literature is Caesalpinia sappan L. of the family Leguminosae. It is commonly known as sappan and is naturally available throughout Asia. The present study aimed to evaluate the antidiabetic action of C. sappan heartwood in alloxan-induced diabetic rats. The objective of the present study was to prepare an ethanolic extract of C. sappan heartwood through soxhlation and determine the antidiabetic activity of the extract on male Wistar rats and compare the potency of the extract with the standard drug glibenclamide. The changes in the body weight of the rats and various analytical parameters like blood glucose, SGOT, SGPT, triglycerides, cholesterol, LDL, and VLDL were also analyzed. To assess the antidiabetic activity, Ethanolic Extract of C. Sappan Linn. (EECS) was used at a dose of 250mg/kg body weight and administered orally for 21 days to Alloxan-induced diabetic rats. The blood glucose was measured using one touch glucometer (Accu check). Statistical comparison among all groups was performed by using ANOVA. The ethanolic extract significantly (p<0.001) reduced the blood glucose, total cholesterol, and triglycerides levels compared with standard glibenclamide 0.5mg /kg body weight. The obtained results have shown that the C. sappan ethanolic extract has antidiabetic activity. They also showed improvement in parameters like body weight and serum lipid profiles. So, it might be of valuable importance in treating Type II diabetes mellitus.